Indigenous Higher Education Student Equity: Focusing on What Works - Devlin, Marcia (The Australian Journal of Indigenous Education, 2009)
Abstract The rates of higher education access, participation and completion for Indigenous students are much lower than those for non-Indigenous students in Australia. This paper argues for a research-led focus on what works in terms of Indigenous student equity in higher education. Undertaking independent evaluation of existing initiatives and leveraging the experience of hundreds of successful Indigenous graduates, it may be possible to articulate some of the ways in which success has been, and can be, achieved, despite the challenges that face Indigenous students. In other words, it may be possible to articulate some aspects of what works for some Indigenous people in relation to higher education. A focus on articulating strategies that Indigenous individuals and communities might adopt in relation to higher education should be developed alongside the management of systemic problems through a range of means. The “success-focused” approach would provide one of a suite of approaches that may be helpful in addressing Indigenous student equity.